PENGARUH DESENTRALISASI, PERSEPSI KETIDAKPASTIAN LINGKUNGAN, AKUNTABILITAS PUBLIK, BUDAYA ORGANISASI TERHADAP KINERJA MANAJERIAL MELALUI SISTEM AKUNTANSI MANAJEMEN (Studi Empiris Pada Rumah Sakit Di Provinsi Banten) - Nurhayadi, Willy; Ismail, Tubagus (Pascasarjana Universitas Sultan Ageng Tirtayas, 2017)
The purpose of this research is to analyze the effect of Decentralization, Perceived Environmental Uncertainty, Public Accountability, Organizational Culture to Managerial Performance Through Management Accounting System. The data used in this study was obtained from the managerial hospital in Banten Province. Of the 248 questionnaires distributed, the number of returned questionnaires and can be processed 169 questionnaires (68.15%). Data is processed by using software program Analysis of Moment Structure (AMOS) Version 16. This research uses purposive sampling method with middle level management and lower level management sample. Sources of data obtained from field research, namely by distributing questionnaires to obtain primary data and research library (Library Research) / documentation. The results showed 1) decentralization has a significant positive effect on the management accounting system; 2) perceived environmental uncertainty has a significant positive effect on management accounting system; 3) public accountability has a significant positive effect on the management accounting system; 4) organizational culture have a significant positive effect on management accounting system; And 5) management accounting system has a significant positive effect on managerial performance.Keywords: decentralization, perceived environmental uncertainty, public accountability, organizational culture, management accounting systems, managerial performance